2018
DOI: 10.1002/hyp.13156
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of forest structure on precipitation interception and run‐off generation in a semiarid region in northern China

Abstract: Water resource scarcity and uneven distribution are 2 major environmental issues in China today. Forest structure is a dominant factor that influences hydrological processes, but the specific interactions remain uncertain due to the predominant use of individual or 1-dimensional forest structure metrics in previous studies. In this study, forest structures in 8 run-off plots on Mount Miaofeng in north China were parameterized by metrics of different dimensionalities. The relation between canopy interception an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
(105 reference statements)
0
23
0
Order By: Relevance
“…This was because low intensity P's were likely to be retained at the soil surface layer (Li et al 2016). The variability in SM of the surface layer was even more distinct in Bansigad catchment, showing low interception losses due to degraded forest, resulting in a large proportion of rainfall reaching the ground surface (Venkatraman and Ashwath 2016;Liu et al 2018) and therefore, the Bansigad catchment showed higher (4%, annually) moisture regimes in surface layer than that for Arnigad (Fig. 7b).…”
Section: Soil Moisture Variation At Different Soil Profilesmentioning
confidence: 94%
“…This was because low intensity P's were likely to be retained at the soil surface layer (Li et al 2016). The variability in SM of the surface layer was even more distinct in Bansigad catchment, showing low interception losses due to degraded forest, resulting in a large proportion of rainfall reaching the ground surface (Venkatraman and Ashwath 2016;Liu et al 2018) and therefore, the Bansigad catchment showed higher (4%, annually) moisture regimes in surface layer than that for Arnigad (Fig. 7b).…”
Section: Soil Moisture Variation At Different Soil Profilesmentioning
confidence: 94%
“…This was because when rainfall amount was too small, most of them were retained on the surface layer only (Li et al, 2016). The difference in SM at surface layer was even more distinct at Bansigad catchment, shows low interception losses due to degraded forest at Bansigad, resulting large volume of rainfall could reach to the ground surface (Liu et al, 2018;Venkatraman and Ashwath, 2016) and therefore, the Bansigad catchment shows higher (4%, annually) moisture regimes at surface layer than Arnigad (Fig. 7B).…”
Section: Soil Moisture Functioning At Different Soil Profilesmentioning
confidence: 96%
“…The influences on precipitation mainly manifest in the canopy interception and stem redistribution of precipitation, of which the canopy interception is mainly affected by vegetation types, canopy density and forest structure complexity [57][58][59].…”
Section: Basic Theorymentioning
confidence: 99%